Constitutional deletion of chromosome 20q in two patients affected with albright hereditary osteodystrophy. - Aldred, M; Aftimos, S; Hall, C; Waters, K; Thakker, R; Trembath, R; Brueton, L (2002)
Albright hereditary osteodystrophy (AHO) results from heterozygous inactivation of G(s)alpha, encoded by the GNAS1 locus on the distal long arm of chromosome 20. This autosomal dominant condition is characterized by short stature, obesity, shortening of the metacarpals and metatarsals, and variable mental retardation and may also include end-organ resistance to multiple hormones. Small insertions and deletions or point mutations of GNAS1 are found in approximately 80% of patients with AHO. The remainder may be accounted for by larger genomic rearrangements, but none have been reported to date. We now describe two patients with constitutional 20q deletions and features of AHO. Such deletions are rare in the published literature and have not previously been associated with AHO. Molecular genetic analysis confirmed complete deletion of GNAS1 in both patients. Parental origin could be determined in both cases and provides further support for the parent-of-origin effect on the biochemical status of patients with AHO.